Looking back: forward looking. Issue 9 (24th July 2017) - Edmunds, Scott C.; Nogoy, Nicole A.; Zauner, Hans; Li, Peter; Hunter, Christopher I.; Zhe, Xiao Si; Goodman, Laurie
Abstract: GigaScience is now 5 years old, having been launched at the 2012 Intelligent Systems for Molecular Biology conference. Anyone who has attended what is the largest computational biology conference since then has had the opportunity to join us for each birthday celebration—and receive 1 of our fun T-shirts as a party prize. Since launching, we have pushed our agenda of openness, transparency, reproducibility, and reusability. Here, we look back at our first 5 years and what we have done to forward our open science goals in scientific publishing. Our mainstay has been to create a process that allows the availability and publication of as many "research objects" as possible to create a more complete way of communicating how the research process is done.